Barack Obama the voice of an American leader - Price, Joann F. (Greenwood Press, 2009)
By any measure, the 2008 presidential race has been historic. The race has created an enthusiasm and a high degree of interest in politics few have ever seen before. At the center of the race is Barack Obama, the first African American to become the presumptive Democratic nominee. Many Americans agree with his politics, and many don't, but most agree he is an incredible force in today's highly-charged political world, and has come along at one of the most crucial, difficult times in our nation's history. For a sense of what has transpired in this campaign and how it is different from others in.